Spiritual Acceptance, Role Transition, and Internalised Paternal Values: Phenomenological Narratives of Self-Esteem Reconstruction Among Fatherless Young Adults and Implications for Bereavement Education in Indonesia - Adiya Alifa Yuniar; Nurul Intan Willyanti; Fitriani Zuhrotin; Ninawati Ninawati (International Journal of Educational Narratives, 2026)
Background. Paternal death during early adulthood disrupts a central relational anchor of self-esteem at a developmental stage that already demands identity consolidation and role independence. Indonesian government data document a substantial population of orphaned children and single-parent households, yet how young adults who lose fathers to death specifically reconstruct self-esteem within Indonesia’s Islamic, collectivist cultural setting remains sparsely documented in the phenomenological literature. Purpose. This study offers a grounded, in-depth account of the self-esteem reconstruction process among three Indonesian young adults (ages 19 to 29) bereaved of their fathers, focusing on the mechanisms rather than only the outcomes of this process. Method. A descriptive phenomenological design was used. Three purposively selected participants domiciled in Banjarmasin, Jakarta, and Cimahi took part in semi-structured, in-depth online interviews; four researchers coded independently before reaching consensus. Trustworthiness was supported by member checking, triangulation with field notes, and an audit trail. Results. Seven themes emerged: emotional dynamics and empathy, spiritual self-acceptance, responsibility and independence, new prosocial life purpose, father as an internalised role model, paternal recognition as a self-worth anchor, and emotional regulation difficulties. Conclusion. Within the scope of this three-participant study, the findings suggest that spiritual meaning-making may function as a culturally specific restoration mechanism within the Dual Process Model, that ante-mortem paternal recognition can operate as an intrapsychic self-esteem buffer, and that gender role expectations shape how role transitions after paternal bereavement affect self-esteem. These patterns are offered as analytically transferable propositions for a specific cultural context rather than as generalisable claims.